A Qualitative Assessment of Islamic Social Finance and Village Funds on the Poverty Level during the Covid-19 Pandemic - Farhan Hadrawi; Thuba Jazil (Universitas Darussalam Gontor, 2024)
This study aims to examine the role of Islamic social finance funds i.e. Zakat, Infaq, Shadaqah, Waqf, and village funds on the poor’s financial viability during the Covid-19 pandemic. The study employs a qualitative method. Data collection in this study was obtained from field observations and in-depth interviews with informants. The informants were classified into three categories: government representatives, Islamic social finance experts, and the recipients of funds in Bogor Regency. This research uses Miles & Huberman's qualitative data analysis technique. This study shows that Islamic social funds and village funds impact the poverty level of the poor impartially. However, Islamic social finance and village funds could assist the poor’s financial viability and provide capital for business during the pandemic. To have an impactful program, the experts suggested an integrated scheme of institutional collaboration and community consolidation.